All about the marine/sea ice diatom Nitzschia lecointei - Wulff, Angela; Torstensson, Anders; Hedblom, Mikael; Andersson, Jenny; Andersson, Mats X.; Jiménez-Gámez, Carlos (My University, 2018)
Generally, in terms of growth N. lecointei seems quite tolerant to changes in pH and pCO2, probably due to the fact that this species grows in an environment with large seasonal variations in the carbonate system. However, increased pCO2 resulted in physiological changes that may have important ecological consequences, such as cellular stoichiometry. For instance, we observed changes in carbon metabolism, and fatty acid content and composition, that did not affect the growth rate. When the experimental period was increased (194 days, ca. 60 asexual generations), we observed a small reduction in growth at 960 µatm pCO2 after 147 days. Carbon metabolism was significantly affected, resulting in higher cellular release of dissolved organic carbon. When studying the synergism between temperature (−1.8 and 2.5°C) and pCO2 (390 and 960 μatm), synergism was detected in growth rate and acyl lipid fatty acid content. Carbon enrichment only promoted (3 %) growth rate closer to the optimal growth, but not at the control temperature (−1.8°C). Optimal growth rate was observed around 5°C in a separate experiment. The total content of fatty acids was reduced at elevated pCO2, but only at the control temperature. PUFAs were reduced at high pCO2. When combining increased temperature and different salinity conditions, the growth rate was higher at 3°C than at -1.8°C. Salinity 10 clearly limited growth rate and the highest growth rates were found at salinity 20 and 35. In another experiment, high and low temperature together with treatments simulating ice formation and melting conditions were studied. Here, the highest levels of oxidative stress were found in low temperature and ice melting treatments, respectively. With respect to 9 weeks in the dark, cell numbers were higher at -1.5°C compared to 3°C, but when retrieved to light conditions, after one week higher cell numbers were observed at 3°C versus -1.5°C. Furthermore, cell numbers were lower when acetate
Keywords: Cambios climáticos; Diatom; Nitzschia lecointei; Climate change; Sea ice